MODEL PEMBELAJARAN SCL GROOVING BERBASIS TEKNOLOGI INFORMASI DI SEKOLAH DASAR - Endi Sutrisna; Baehaki; Sakti Handayani; Dethia HS Suci Nurani; Siti Laela (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The paradigm shift from teacher-centered to student-centered learning demands that teachers continuously innovate to create effective, engaging, and up-to-date learning experiences. This article aims to describe and analyze the innovation of the "Grooving" learning model (Alur Bahagia – "Happy Flow"), a student-centered learning (SCL) model integrated with information technology (IT) at the elementary school level. This research employed a descriptive qualitative approach using a case study method. The subjects were classroom teachers and 28 students at a public elementary school in Pandeglang, Banten, Indonesia. Data were collected through participatory observation, in-depth interviews, and analysis of instructional documents. The findings indicate that the Grooving model has a structured syntax consisting of four learning flows designed in stages from light to complex instruction, integrating interactive media such as videos, online assessment platforms (Wordwall, Liveworksheets), and virtual maps. The implementation of this model proved to enhance students' learning motivation, critical thinking skills, and learning outcomes in the cognitive, affective, and psychomotor domains. The Grooving model offers practical contributions in the form of concrete guidance for teachers to implement structured, technology-based SCL. This study recommends further trials on a larger scale and across various subjects to quantitatively test its effectiveness. Keywords: Grooving, student-centered learning, technology-based learning, elementary school, learning innovation